2021
DOI: 10.1038/s41598-021-85001-2
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD321 antibody immunotherapy protects liver against ischemia and reperfusion-induced injury

Abstract: The prognosis of the liver transplant patients was frequently deteriorated by ischemia and reperfusion injury (IRI) in the liver. Infiltration of inflammatory cells is reported to play critical roles in the pathogenesis of hepatic IRI. Although T lymphocytes, neutrophils and monocytes infiltrated into the liver underwent IRI, we found that neutrophil depletion significantly attenuated the injury and serum liver enzyme levels in a murine model. Interestingly, the expression of CD321/JAM-A/F11R, one of essential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Results also showed that there was decreased hepatocyte necrosis and apoptosis, and decreased upregulation of TNF-alpha and IL-6 in the mice that received anti-CD321 mAb after liver IRI. Therefore, the blockade of CD321 may serve as a potential therapy in reducing the inflammation and liver injury seen after liver IRI [ 36 ].…”
Section: Neutrophil Trafficking Via Cellular Adhesion Molecules and C...mentioning
confidence: 99%
“…Results also showed that there was decreased hepatocyte necrosis and apoptosis, and decreased upregulation of TNF-alpha and IL-6 in the mice that received anti-CD321 mAb after liver IRI. Therefore, the blockade of CD321 may serve as a potential therapy in reducing the inflammation and liver injury seen after liver IRI [ 36 ].…”
Section: Neutrophil Trafficking Via Cellular Adhesion Molecules and C...mentioning
confidence: 99%
“…JAM-A (CD321) is involved in cell adhesion and tight junction formation. It can influence inflammatory responses by regulating leukocyte migration and barrier function [ 60 ]. Similarly to E-Cadherin, we found that placental JAMA-A was decreased at all study periods when animals were treated with SHS (1.1-fold, p < 0.002; 1.8-fold, p < 0.0002) or eCigs (both at 1.1-fold, p < 0.02, Figure 7 C).…”
Section: Resultsmentioning
confidence: 99%
“…Since depleting neutrophils completely may not be clinically feasible, given their role in pathogen clearance and immune surveillance, a better approach may be to block circulating leukocytes from entering the inflammatory site selectively. Indeed, a recent study took this approach when mAb treatment blocked vascular surface marker CD321 (also known as junctional adhesion molecule A or F11R), a marker for transmigration of circulating leukocytes into the inflamed tissue [19 ▪▪ ]. Damage responses by hepatic IRI, evaluated by serum liver enzymes, inflammatory cytokines, and hepatocyte cell death, were all attenuated by the CD321 blockade.…”
Section: Graft-infiltrating Polymorphonuclear Neutrophils and Macroph...mentioning
confidence: 99%